Kaul Kemiskinan Masa Kini: Makna, Tantangan dan Pembinaannya - Ekanisius Dediyanto; Gregorius Hertanto Dwi Wibowo (Jurnal Seri Mitra (Refleksi Ilmiah - Pastoral), 2023)
There is a difference between consecrated people and people in general in living poverty. In the lives of those who take vows, poverty is taken knowingly and willingly as a way to imitate the life of Jesus, their teacher. Different from world poverty which is often passively accepted, the practice of poverty in consecrated life is seen as an ideal life that is inspired by the practice of Jesus' poverty. The reality of poverty in the world is generally fatalistic, where poverty is often a result of injustice, oppression, colonialism, fraud, and many other manipulative practices. On the other hand, in the vows of poverty, simplicity, and lack of self-sufficiency are deliberately chosen, so that people will not be attached to worldly possessions, both for the sake of getting closer to holiness and so that they can be in solidarity with others. In addition, the vow of poverty is also lived in order to develop the lives of the poor. The question is whether the ideal of poverty can still be lived in today. The world of technology and the advancement of various facilities have penetrated behind the monastery fence. The lifestyles of consecrated people today are also changing. Facilities in the monastery such as buildings, means of transportation, means of communication, money and other facilities appear to be better and fully available. Do all these conveniences not obscure the meaning of the vow of poverty? This article attempts to reveal the practice of living the vows of poverty among today’s young religious men/women, and from there it tries to offer appropriate forms of coaching and mentoring to assist young religious men/women in living the vows of poverty.